2023
DOI: 10.1021/jacs.3c07727
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Coley’s Toxins: Immunogenic Cardiolipins from Streptococcus pyogenes

Yern-Hyerk Shin,
Sunghee Bang,
Sung-Moo Park
et al.

Abstract: Coley's toxins, an early and enigmatic form of cancer (immuno)therapy, were based on preparations of Streptococcus pyogenes. As part of a program to explore bacterial metabolites with immunomodulatory potential, S. pyogenes metabolites were assayed in a cell-based immune assay, and a single membrane lipid, 18:1/18:0/18:1/18:0 cardiolipin, was identified. Its activity was profiled in additional cellular assays, which showed it to be an agonist of a TLR2−TLR1 signaling pathway with a 6 μM EC 50 and robust TNF-α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
(86 reference statements)
0
5
0
1
Order By: Relevance
“…This stimulation led to a robust induction of TNF-α, signifying potential implications for immune regulation and cancer immunotherapy. 216 Research has shown that there is a close association between Streptococcus and the occurrence and development of head and neck cancer. 214 , 217 A recent study found that S. anginosus is elevated in patients with OSCC, highlighting the continued relevance of this bacterium in the carcinogenesis of the oral cavity.…”
Section: Overview Of Oral Microbiota In Carcinogenesismentioning
confidence: 99%
“…This stimulation led to a robust induction of TNF-α, signifying potential implications for immune regulation and cancer immunotherapy. 216 Research has shown that there is a close association between Streptococcus and the occurrence and development of head and neck cancer. 214 , 217 A recent study found that S. anginosus is elevated in patients with OSCC, highlighting the continued relevance of this bacterium in the carcinogenesis of the oral cavity.…”
Section: Overview Of Oral Microbiota In Carcinogenesismentioning
confidence: 99%
“…Cancer immunotherapy heralds a promising revolution in the realm of oncological treatments. This groundbreaking approach, rooted in historical milestones like "Coley's toxins" [1] and, later, the identification of cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4), has consistently showcased the potential to redefine cancer treatment paradigms [2][3][4]. As we deepened our understanding of tumor antigens and immune-tumor interactions in the latter half of the 20th century, the emergence of agents targeting CTLA-4, programmed cell death protein 1 (PD-1), and programmed death-ligand 1 (PD-L1) pathways marked 2 of 18 significant successes in treating a range of malignancies [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Diese Herausforderung wird noch deutlicher, wenn es sich um Lipide mikrobiellen Ursprungs handelt, da diese häufig bisher unbeschriebene strukturelle Veränderungen und hochspezifische Struktur-Aktivitäts-Profile aufweisen, [12][13][14] für die authentische Standards meist nicht verfügbar sind. [15][16][17] Die Vorhersagbarkeit von relativen Molekülstrukturen von Lipiden allein auf der Grundlage von MS-Daten ist daher meist noch zu unpräzise und kann zu lückenhaften oder fehlerhaften wissenschaftlichen Schlussfolgerungen führen.…”
unclassified